2008
DOI: 10.1016/j.bbalip.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Sharpening the edges of understanding the structure/function of the LPA1 receptor: Expression in cancer and mechanisms of regulation☆

Abstract: Since the molecular cloning of the vzg-1/Edg-2/LPA1 gene, studies have attempted to characterize LPA1 receptor functionality into a single categorical role, different from the other Edg-family LPA receptors. The desire to categorize LPA1 function has highlighted its complexity and demonstrated that the LPA1 receptor does not have one absolute function throughout every system. The central nervous system is highly enriched in the LPA1 receptor, suggesting an integral role in neuronal processes. Metastatic and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 95 publications
3
35
0
Order By: Relevance
“…Whereas LPA 1 plays a very important role in migration of breast, pancreatic, and prostate cancer cells (25,26), our data suggest that LPA 2 and LPA 3 are more important in cell adhesion, migration, and invasion of EOC cells, which are consistent with reports showing that LPA 1 is involved in the negative growth regulation in ovarian cancer cells and that LPA 2 and LPA 3 , but not LPA 1 , expression is up-regulated in last-stage EOC (27). In addition, we have shown that either inhibitors and/or dominantnegative forms of G i protein, phosphatidylinositol 3-kinase, or cytosolic phospholipase A 2 (cPLA 2 ) completely or nearly completely block LPA-induced cell migration in human EOC cells, suggesting that these three molecules play a pivotal role in this process (2,10,11,24).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Whereas LPA 1 plays a very important role in migration of breast, pancreatic, and prostate cancer cells (25,26), our data suggest that LPA 2 and LPA 3 are more important in cell adhesion, migration, and invasion of EOC cells, which are consistent with reports showing that LPA 1 is involved in the negative growth regulation in ovarian cancer cells and that LPA 2 and LPA 3 , but not LPA 1 , expression is up-regulated in last-stage EOC (27). In addition, we have shown that either inhibitors and/or dominantnegative forms of G i protein, phosphatidylinositol 3-kinase, or cytosolic phospholipase A 2 (cPLA 2 ) completely or nearly completely block LPA-induced cell migration in human EOC cells, suggesting that these three molecules play a pivotal role in this process (2,10,11,24).…”
Section: Introductionsupporting
confidence: 81%
“…4). To date, at least six LPA receptors have been identified (27). These receptors may have overlapping or even opposing effects in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, ovarian cancer show a significant reduction in LPA1 levels as compared with normal tissues . In addition, LPA2 and LPA3 appear to have a greater role in ovarian cancer aggressiveness as compared with LPA1 (Sengupta et al, 2003;Ren et al, 2006;Murph et al, 2008;Yu et al, 2008). In our current study, we demonstrated higher levels of LPA1 transcripts in HCC cells than that of LPA2 or LPA3.…”
Section: Discussionmentioning
confidence: 99%
“…LPA 1 is a member of the endothelial differentiation gene family (Hecht et al, 1996;An et al, 1997) and exhibits widespread tissue distribution with high levels of expression in the brain, heart, small intestine, kidney, ovary, testis, prostate, colon, thymus, and pancreas (Yang et al, 2002;Anliker and Chun, 2004). Furthermore, increased LPA 1 signaling has been implicated in a number of disease processes (Shida et al, 2003;Inoue et al, 2004;Boucharaba et al, 2006;Murph et al, 2008;Pradère et al, 2008;Tager et al, 2008), making this receptor a novel target for therapeutic intervention. However, there are currently no selective LPA 1 antagonists being used clinically.…”
Section: Parametermentioning
confidence: 99%